Field-and clinically derived estimates of Wolbachia-mediated blocking of dengue virus transmission potential in Aedes aegypti mosquitoes - Simmons, Cameron (2018)
The wMel strain of Wolbachia can reduce the permissiveness of Aedes aegypti mosquitoes to disseminated arboviral infections. Here, we report that wMel-infected Ae. aegypti (Ho Chi Minh City background), when directly blood-fed on 141 viremic dengue patients, have lower dengue virus (DENV) transmission potential and have a longer extrinsic incubation period than their wild-type counterparts. The wMel-infected mosquitoes that are field-reared have even greater relative resistance to DENV infection when fed on patient-derived viremic blood meals. This is explained by an increased susceptibility of field-reared wild-type mosquitoes to infection than laboratory-reared counterparts. Collectively, these field- and clinically relevant findings support the continued careful field-testing of wMel introgression for the biocontrol of Ae. aegypti-born arboviruses.